The species–area relationship in ant ecology - Ohyama, Leo (2021)
AIM: The positive relationship between species richness and area-the species-area relationship (SAR)-is a key principle in ecology. Previous studies show large variation in the SAR across taxa collectively indicating the necessity of a taxon-focused approach to accurately evaluate biodiversity scaling patterns. Ants are ideal for this given their global distribution and role in ecosystem functioning. Using data from insular ant communities, this study quantified and investigated various attributes of ant SARs and reviewed the SAR literature for ant faunas, world-wide, to identify specific areas for improvement. LOCATION: Islands around the world. TAXON: Ants (Hymenoptera: Formicidae). METHODS: We aggregated data on species richness and island characteristics from previous studies on ant SARs to evaluate effects of climate, biogeographic realm, and latitude on slope values from these studies. A multimodel inference approach was used to determine the form of the different SARs, and whether there were any differences between mainland and insular SARs. We also assessed differences between mainland and insular SAR slopes and intercepts. To seek a general slope coefficient for ants, we used a mixed-effect model. Finally, we tested for potential thresholds in the global insular SAR using piecewise regression models. RESULTS: There was a negative relationship between SAR slopes and precipitation in both mainland and insular SARs, while SAR slopes and intercept values were higher in mainland compared to insular systems. Strong evidence of thresholds emerged in the global insular SAR. Finally, a general slope of 0.16 was observed for insular systems, which is lower than found in previous studies. MAIN CONCLUSIONS: A taxon-focused approach proves to showcase unexpected patterns in the SAR. Ant diversity increases faster across area in mainland areas compared to true islands. The influences of climate and biogeographic realms on the ant SAR warrant deeper study. Our review highlights knowledge gaps in the ant SAR that also extend to other taxa, such as the effects of nonnative species on the SAR.